Perancangan Sistem Informasi Data Kependudukan Berbasis Web pada Kelurahan Lokoboko Kecamatan Ndona - Stefania Baptis Seto; Astria Binti Musa; Sofia Sa'o; Finsensius Yesekiel Naja; Agustina Mei; Ningsih Ningsih; Maria Trisna Wondo; Maria Fatima Mei (LPPM Universitas Flores, 2022)
The problem found in Lokoboko Village, Ndona sub-district is that village data input is still done manually and has not been regulated properly, therefore this community service program is very good for changes in village data management that has been carried out by village officials. With the design of this Web-based data information system, it is very easy for village officials to input and manage population data. The purpose of this service activity is to provide convenience to village officials in filling village data using the HTML website. The method used in this service activity is socialization, assistance and training to village officials in using HTML Web sites. The results obtained are that data taken from the community is inputted via a web created and the data is well organized so that it can be presented neatly.